Sumoylation and phosphorylation: hidden and overt links - Tomanov, Konstantin; Nukarinen, Ella; Vicente, Jorge; Mendiondo, Guillermina M.; Winter, Nikola; Nehlin, Lilian; Weckwerth, Wolfram; Holdsworth, Michael J.; Teige, Markus; Bachmair, Andreas (Oxford University Press, 2018)
Post-translational modifications are essential mediators between stimuli from development or the environment and adaptive transcriptional patterns. Recent data allow a first glimpse at how two modifications, phosphorylation and sumoylation, act interdependently to modulate stress responses. In particular, many components of the SUMO conjugation system are phosphoproteins, and some regulators and enzymes of protein phosphorylation can be sumoylated. Equally important, however, a number of proteins can be subject to both modifications. These substrates also have the capacity to connect stimuli transmitted via sumoylation with those transmitted via phosphorylation. As a prime example, we review data suggesting that nitrate reductase is a hub that integrates cues from these two modifications. Powerful proteomics approaches allowed the identification of additional common substrates, paving the way for studies to understand, on a broader basis, the cross-talk of phosphorylation with sumoylation and how it contributes to plant growth.